Experimental Gingivitis in Male Khat (Catha edulis) Chewers - Al-Hebshi, Nezar Noor; Al-Ak’hali, Mohammed Sultan (International Academy of Periodontology, 2010)
Whether or not khat chewing is detrimental to the periodontium remains uncertain. Findings from cross-sectional studies have been contradictory and, in most cases, uncontrolled for confounders. Objectives: to experimentally test the effect of khat chewing on formation of dental plaque and development of gingivitis. Methods: This was a split-mouth, parallel-group, 20-day experimental gingivitis study involving non-smoking, young, male khat chewers (n = 8) and non-chewers (n = 9). Measurements of plaque index (PI), gingival index (GI), and bleeding on probing (BOP), as experimental outcomes, were performed on days 0, 10, and 20. Scores were compared between the two groups (parallel-group model) and between the khat-chewing and non-chewing sides (split-mouth model). Results: All experimental outcomes significantly increased over time. Results from the two models were consistent. Khat chewing was associated with lower PI scores; however, differences were only significant at day 20. Despite scoring higher in baseline gingival inflammation, the khat chewers and khat-chewing sides showed significantly lower GI and BOP scores at days 10 and 20. The effect of khat chewing was evident on both the lingual and buccal aspects. Conclusions: The observed anti-plaque and anti-gingivitis properties indicate that khat chewing is probably not detrimental to the periodontium. The validity of previous findings supporting an opposite view is undermined by lack of control for confounders, particularly smoking.